The public health and economic consequences of unintended pregnancies in South Africa - Hoa H. Le; Mark P. Connolly; Jingbo Yu; Yacob Pinchevsky; Petrus S. Steyn (PAGEPress Publications, 2015)
Unintended pregnancy (UIP) poses considerable humanistic and economic burden in both developed and developing countries. In the analysis described here, we evaluate the costs of unintended pregnancies based on estimates in South Africa. To estimate the burden of UIP, a decision-analytic model was developed using probabilities for pregnancy related outcomes related to UIPs in a single year, which included miscarriage, ectopic pregnancy, abortion and live birth. Costs to the public health system were estimated for each birth outcome. We estimated 636,040 annual unintended pregnancies. The annual maternal deaths were estimated to be 1134 of which 219 (19.3%) are attributed to abortions and 915 (80.7%) attributed to complications from miscarriages, ectopic pregnancies and deliveries. The costs attributed to UIP birth outcomes accounted for 3.42 billion Rand annually. Annual costs of UIP live births were estimated to be 82.8% of the total costs with abortion and miscarriage accountable for 8.3% and 8.4% of costs, respectively. In conclusion, despite weaknesses of modelling approaches in healthcare, we believe that our findings here will support further preventative initiatives in South Africa and more broadly to improve access to affordable and effective contraception.